Pengembangan Pengelolaan Usaha Penyulingan Minyak Sereh Melalui Pelatihan Budidaya, Teknik Penyulingan dan Hiliriasi Produk Sereh Wangi (Andropogon nardus L) Desa Tempursari - Wardani, Arief Kusuma; Agusta, Herma Fanani; Hasani, Rofi Abul; Nofitriana, Risma; Permatasari, Sukma Putri; Listiyani, Oktavia (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Low human resources are the main reason the citronella oil refining business in Tempursari village, Candimulyo, Magelang, which started in 2021, has stopped producing citronella oil. The quality of lemongrass essential oil is an indicator of success in the distillation process. Lemongrass oil is said to be of quality if it has a high yield and complies with (SNI) 06-3593-1995. To increase the community's knowledge and skills, a series of outreach activities, cultivation training, distillation techniques, making citronella solid soap products and practice of managing a website as promotional media were carried out. The focus of this service involves the participation of the community who are members of the Association of Farmer Groups, the Women's Farmer Community and Karangtaruna of Tempursari Village, Candimulyo District, Magelang Regency. The results of increasing knowledge and skills include the percentage of pre- and post-test scores which show an increase in knowledge of citronella cultivation from 62.68% to 71.33% and post-harvest knowledge from 38.02% to 82.50%. The level of improvement in distilling skills was shown by an increase in yield from 0.1% to 0.8%, partner skills also increased because they succeeded in making citronella solid soap, and Karangtaruna was able to control the operations of the website www.atsiri-tempursari.com so that the latest information could be conveyed through the media digital.